A case report of surgical resection treatment for complete remission after chemotherapy for advanced pancreatic cancer - Zhang, Zhongyan; Lin, Hongfeng; Li, Hehe; Wang, Xin (Frontiers in Oncology, 2023)
Pancreatic cancer is a common type of cancer that is treated using surgery or chemotherapy. However, for patients who cannot have surgery, the treatment options are limited and have a low success rate. We report a case of a patient with locally advanced pancreatic cancer who was unable to have surgery due to a tumor that had invaded the coeliac axis and portal vein. However, after receiving chemotherapy with gemcitabine plus nab-paclitaxel(GEM-NabP), the patient achieved complete remission, and a PET-CT scan confirmed that the tumor had disappeared. Eventually, the patient underwent radical surgery with distal pancreatectomy with splenectomy, and the treatment was successful. This case is rare, and there are few reports of complete remission after chemotherapy for pancreatic cancer. This article reviews the relevant literature and guides future clinical practice.